1985
DOI: 10.1111/j.1445-2197.1985.tb00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐proctectomy Perineal Hernia: Case Report and Discussion

Abstract: Perineal hernia is a rare complication of pelvic surgery. Women are more commonly affected, and development of the condition is usually gradual. Although the true incidence of this problem is unknown, few cases are severe enough to require operative repair. We report the experience of one of the authors (E.S.R.H.) in postproctectomy perineal hernia. One case required surgical repair and is presented, with a discussion of the operative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Since then, other publications have appeared in the literature, but mostly as case reports [8,[13][14][15]18]. The frequency of symptomatic perineal hernia after abdominoperineal resection ranges from 0.13 to 0.9% [7,20,27]. Asymptomatic hernias are much more common, with a frequency of approximately 7% [17].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since then, other publications have appeared in the literature, but mostly as case reports [8,[13][14][15]18]. The frequency of symptomatic perineal hernia after abdominoperineal resection ranges from 0.13 to 0.9% [7,20,27]. Asymptomatic hernias are much more common, with a frequency of approximately 7% [17].…”
Section: Discussionmentioning
confidence: 97%
“…Other authors used muscular flaps of the fascia lata, gracilis, rectus abdominis, and gluteus maximus to close the pelvic defect [5,12,18,23]. Nonabsorbable mesh, as in other hernia repairs, is being used increasingly for perineal hernia repairs; it provides a new pelvic floor in cases of large defects [1,4,10,13,15,20,27]. From many years of mesh use for repair of extraperitoneal inguinal hernias, we have determined that the mesh is a promising and credible tool [11].…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Asymptomatic perineal hernias are much more common, with a reported frequency of 7%. 13 Our search of the literature found only one report describing two cases of perineal hernia after laparoscopic APR (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…16 Postoperative perineal hernias still remain uncommon events. Two recently published articles by So et al 6 and McMullin et al 18 reported incidences of 0.62 and 0.9 percent, respectively. In this report, two cases are described in which symptomatic perineal hernias occurred after a laparoscopic abdominoperineal resection.…”
Section: Discussionmentioning
confidence: 96%